2017
DOI: 10.1002/ams2.273
|View full text |Cite
|
Sign up to set email alerts
|

Performance review of regional emergency medical service pre‐arrival cardiopulmonary resuscitation with or without dispatcher instruction: a population‐based observational study

Abstract: BackgroundTo investigate variations in emergency medical service (EMS) pre‐arrival cardiopulmonary resuscitation (CPR), including both bystander CPR without dispatch assistance and dispatch‐assisted CPR (DACPR).MethodsWe carried out an observational study by implementing EMS pre‐arrival CPR reports in three fire agencies. We included adult, non‐traumatic, and non‐EMS witnessed out‐of‐hospital cardiac arrests. This reporting system comprised the dispatch instruction process and bystander CPR quality based on ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…is may be attributed to urban citizens being younger in Taichung [17], which is similar to that observed in previous studies [3,5,12,13,18]. Additionally, the government implemented resuscitation curriculum in schools.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…is may be attributed to urban citizens being younger in Taichung [17], which is similar to that observed in previous studies [3,5,12,13,18]. Additionally, the government implemented resuscitation curriculum in schools.…”
Section: Discussionsupporting
confidence: 83%
“…However, the time gap between the recognition of cardiac arrest to the arrival of emergency medical technicians (EMTs) is long, and the interventions from bystanders before an EMT's arrival could critically affect the prognosis in these patients [4]. A study showed that bystanders do not perform CPR before an EMT's arrival because of panic, concerns about not performing CPR accurately, fear of harming the individual, fear of legal consequences, and concern about mouth-to-mouth contact [5,6]. e survival rates of patients with OHCA have gradually increased recently through the promotion of the resuscitation training program, simplified CPR process, improved CPR quality by laypersons, and willingness [4].…”
Section: Introductionmentioning
confidence: 99%
“…24 Moreover, continuous coaching for DA-CPR has helped bystanders perform CC properly. 25 As mentioned above, our study revealed that bystander fatigue was higher with using the SFM than with using the flat floor. Thus, bystanders need encouragement in increasing CC depth and rate through DA-CPR to help prevent the adverse effects of using home-bed mattresses.…”
Section: Discussionsupporting
confidence: 63%
“…The OR was 0.74 (0.54-1) for the pediatric group (1 study 26 ) and 1.15 (1.10-1.19) for the adult studies 27,40,43,45 . The heterogeneity was not confirmed in a sensitivity analysis where Goto et al (2014) 25 was replaced by the overlapping study of Akahane et al (2012). 15 For the same outcome, two sensitivity analyses for the comparison of DA-CPR vs. no CPR indicated lower rates of initial shockable rhythm with DA-CPR, while the mainstream analysis and the other 3 of 5 relevant sensitivity analyses indicated higher rates of shockable rhythm with DA-CPR…”
Section: Pediatric Studiesmentioning
confidence: 94%
“…Of the 33 included studies, 15 were conducted in the adult population only 16,20,22,25,27,31,34,37,[41][42][43][44][45]47,49 , five were conducted in the pediatric population ILCOR DA-CPR Systematic Review -Feb 19 2019 10 only 15,18,26,33,40 , and 13 included both adults and children 17,19,21,23,[28][29][30]32,[35][36][37]45,48 . The proportion of males ranged from 52% to 85% (average 66%).…”
Section: Patient Characteristicsmentioning
confidence: 99%